A Study on Incidence of Endophthamitis Post Intravitreal Injections in Southern Punjab Rural Population (Medical Forum Monthly, 2024)
Objective: To evaluate the incidence of endophthalmitis post intravitreal injection in rural population of southern Punjab (Multan District) of anti-vascular endothelial growth factor.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was conducted at Multan Medical and Dental College, Multan between January 2014and December 2015.Materials and Methods: Addresses on National Identity Cards were used to enroll the patients who are residing out of multan municipal area. Patient’s medical records were maintained to identify the incidence of endophthalmitis. Patients presenting with post operative endophthalmitis between January 2014 till December 2015 were included in the study. All IVIs were performed by single surgeon using standard sterile technique in operation theatre settings. None of the patients were prescribed with preoperative topical or systemic antibiotics. Postoperatively all patients had a QDS dose of topical ofloxacin.Results: A total of 416 intravitreal injections were performedduring the study period. All patients had bevacizumab as intravitreal anti vascular growth factor (Anti-VEGF).Out of total patients there were two cases of endophthalmitis. This led to an incidence of 0.48%,(95% confidence interval: 0.0026-0.0220%). These two cases had intravitreal specimens which were later found to be culture negative.Conclusion: The risk of post intravitreal Anti-VEGF in rural southern Punjab was found to be higher than quoted national and international standards though we had a small patient group which demands a similar study with larger sample size.